STRATEGI KOMUNIKASI PENYEBARAN PESAN PERUBAHAN PADA PT. PERTANI (PERSERO) - Elda Clara Sophia; Lilyana Aprianty (Commed : Jurnal Komunikasi dan Media, 2018)
Organizational culture is a belief, custom, value which exist in an organization in order to differ one organization and the other. Affairs in organizational culture unwittingly manage attitudes and behaviors of the organizational doers that its practice affects to the work environments. This research discusses about the practice of organizational culture values that are applied by PT Pertani (Persero) as one of Indonesian State Owned Enterprises after there were changes in Board of Directors. This research aims to find out the organizational change and the distribution of order changes along with the practice of organizational culture values in PT Pertani (Persero). Researcher uses the theory of organizational communication which focuses on organizational change and organizational culture. This is a qualitative descriptive research using the method of in-depth interview and observation. The result of this research is planned organizational changes found in PT Pertani (Persero) with the distribution of change process through tell and sell method in board meeting once a week, identify and reply by involving employees to create the concept of change for company development, and withold and uphold which is electing important information done by management to be distributed to all employees. After committing organizational changes, the practice of organizational culture values in PT Pertani (Persero) is performed based on Board of Directors' instructions which consist of enforcement of new regulations and a more disciplined and assertive way of working as well as advancing employees' rights in a form of income increase.